(untitled) (Law Research Review Quarterly, 2026)
The culture of toxic masculinity is still a significant obstacle in handling rape cases against adult men. The view that men should always be strong and unlikely to be victims leads to low reporting and weak institutional attention. This study aims to analyze the factors of rape of adult men in the struggle of toxic masculinity culture and examine the responsiveness of law in its handling using Nonet and Selznick’s responsive legal theory as an analytical framework. This research uses a qualitative approach with a socio-legal research type, which combines observation, interviews, questionnaires and literature studies. The results of the study show that toxic masculinity functions as a structural barrier that suppresses the victim’s courage to report, triggers the bias of law enforcement officials, and increases the risk of secondary victimization. Although Indonesia’s positive law has moved towards more inclusive victim recognition through the Indonesia Criminal Code Number 1 of 2023, legal implementation still faces challenges in terms of institutional sensitivity and substantive protection of victims. This study emphasizes the importance of strengthening gender-justice-oriented responsive laws in ensuring protection and recovery for adult male rape victims.